2010
DOI: 10.5012/bkcs.2010.31.5.1252
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ag/PVP Nanocomposites as a Solid Precursor for Silver Nanocolloids Solution

Abstract: A polyvinylpyrrolidone (PVP)/Ag nanocomposites was prepared by the simultaneous thermal reduction and radical polymerization route. The in situ synthesis of the Ag/PVP nanocomposites is based on the finding that the silver n-propylcarbamate (Ag-PCB) complex can be directly dissolved in the NVP monomer, and decomposed by only heat treatment in the range of 110 to 130 o C to form silver metal. Silver nanoparticles with a narrow size distribution (5 -40 nm) were obtained, which were well dispersed in the PVP matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The diffraction peaks at 2θ equal to 38.883˚, 45.070˚, 65.191˚, 78.0860 are in good agreement with the literature values of metallic silver [18] [19]. The average grain size (D) of silver can be determined using Debye Scherrer's relation:…”
Section: X-ray Diffraction Studiessupporting
confidence: 84%
“…The diffraction peaks at 2θ equal to 38.883˚, 45.070˚, 65.191˚, 78.0860 are in good agreement with the literature values of metallic silver [18] [19]. The average grain size (D) of silver can be determined using Debye Scherrer's relation:…”
Section: X-ray Diffraction Studiessupporting
confidence: 84%
“…Also, interaction between PVP and cotton was observed by Selvam and Sundrarajan (2012). Additionally, Hong et al (2010) observed broadened and shifted C=O stretching bands of the silver/PVP nanocpomosite compared to the PVP powder band. This was associated with the formation of a coordination bond between the silver and oxygen atoms in the C=O group.…”
Section: Surface Analysismentioning
confidence: 82%
“…Considerable enhancement in the nonlinear refractive index may be attributed to the thermally induced lensing effect in PVP-GNP thin lms. 54,55 The electrons with energy higher than the Fermi energy are called hot electrons. These hot electrons dissipate their excess energy through the scattering process.…”
Section: Nlo Studies Of Colloidal Gnps and Gnp-pvp Nanocompositesmentioning
confidence: 99%